Malraux and Gary Mythomaniacs - Laurent, Thierry (Literatūra, 2022)
Mythomania is not an isolated pathology in psychiatry: it is mixed with other mental disorders. It is not always easy to assess their seriousness or to differentiate them from banal lies; when someone invents a life other than his own without realizing it, he can be called a mythomaniac. Autobiographical literature contains many texts where truth rubs shoulders with fiction; some writers even have a reputation as great storytellers. Malraux and Gary are among them: both in books and in public statements, they shaped their own legend when their lives were already exceptionally rich, even romantic; they practiced autofiction before the letter. It is likely that their dissatisfaction with reality and existential anxieties have fueled this permanent need to falsify self-talk. Malraux mainly practiced self-heroization while Gary, much more capable of self-mockery, had fun wearing different masks and imitating the chameleon.
Keywords: Malraux; Gary; mythomania; confabulation; autofiction; literary fraud